Pengelolaan Bank Sampah dan Pembuatan Pupuk Kompos di Kelurahan Baru ilir Kecamatan Balikpapan Barat - Faisal Manta; Doddy Suanggana; Andre Amba Matarru; Muhammad Ilham Yusnin; Dinda Achmad Feridiansyah; Sony Doran Febriawan; Rafly Amanda; Faradhila Arham Hagan; Saut Hamonangan Mangunsong (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The waste bank management program aims to help the residents' economy and maintain environmental cleanliness by processing waste in the environment. The improvement of the residents' economy is done by selling inorganic/plastic waste that has economic value and converting organic waste into compost. Because of this background, the waste bank program was chosen as a community service activity for 2022 ITK by considering the appropriate location and partners. RT 56 Kelurahan Baru Ilir, West Balikpapan District is a densely populated area with the majority of its residents making seasonal livelihoods such as washermen and construction workers, so with the aim of helping the residents' economy, we decided to make RT 56 a partner for the waste bank program. The waste bank program is implemented in stages, namely coordination with the local government, socialization, waste collection, waste weighing, recording, selling waste and payments to customers. The processing of organic waste consists of refining organic waste, mixing in composting, ripening, harvesting compost. The Waste Bank program was implemented for 3 months, namely in March-May 2022 and obtained 23 customers with total customer funds reaching Rp564,324.00. The organic waste treatment program is carried out by making a composting prototype made from drums that is able to reduce the unpleasant odor produced during the composting process, so that in 1 month, ready-to-use organic fertilizer can be produced.